Towards a New Paradigm for Social Science Research - رجب, إبراهيم (Tafakkur, 1999)
When I first came across a statement to the effect that it normally takes the social sciences fifty years to digest and assimilate any new development in the physical sciences, I took that for some kind of exaggeration. With the modern explosion in communications, the statement seemed too pessimistic to be applicable to the world of today. Not until I came to consider the fate-in the social sciences- of the magnificent developments which have been taking place in the natural sciences since the early decades of this century. These great scientific discoveries, the impact of which is forcing a deep rethinking of science itself, thus leading to the emergence of the “New philosophy of science” have hardly made a dent on the social sciences. What is especially deplorable about this is that these particular developments in the natural sciences should have been of great interest because of their special relevance for the social sciences. They indeed seem to be ushering in a brave new understanding of the nature of matter, human being, and mind. But most social scientists hold a too deep-seated belief in the positivist/ empiricist tradition’s conception of what should constitute “true”  science to allow them to harbor any serious doubts about its validity. For them, it is “ the only”  perspective from which to see and to understand the world. For them, it looks so unscientific, or almost heretical to think otherwise. This recalcitrance, understandably incensed the critics of positivism, who became more defiant and more virulent in their criticism. Since extreme positions - by definition - tend to distort the truth, the critics‘ suggestions to remedy the situation turned out to be the less palatable - even to those who may basically accept the arguments against positivism. Which, in turn, seems to have resulted in an impasse.